O processo de formação dos docentes de Libras nas séries finais do ensino fundamental no município de Tailândia-Pará - FERNANDES, Ducilene Silva (2023)
To be elected as the central theme of this work to train teachers in the teaching of pounds in the final series in the municipality of Thailand, tried to make a critical approach regarding this issue in a context that met the reality of Deaf Education in Brazil and especially in the city of Thailand. For this, we sought to scientificity of the most specific concepts of communication theory in the context of linguistics, historicizing and legal regulatory frameworks both Deaf Education as the academic training of teachers Pounds. In the more specific context of this study, we sought to form a general picture of the situation in which it is the specific teacher training in Pounds and how this training is evolving and changing the reality of teaching in deaf education. Finally, this general framework was extended to the city of Thailand, where it sought to deduce the actual situation of deaf students as both teachers and their performances in local schools within the scope of Deaf Education.